Intracranial Hypotension Syndrome after Lumbar Drainage in Skull Base Surgery: Diagnosis and Correct Management - Baram, Ali; Zaed, Ismail; Safa, Adrian; Robertis, Mario De; Lasio, Giovanni; Maira, Giulio; Cannizzaro, Delia (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Lumbar drainage is commonly used in skull base surgery; however, very few cases of intracranial hypotension syndrome are reported to be caused by this procedure. We present a clinical case of lumbar drainage–assisted orbital and optic canal decompression surgery for a recurrent voluminous spheno-orbital meningioma, together with a literature review. A 49-year-old woman became confused and drowsy on postoperative day 3, after initially experiencing neurologic stability. Computed tomography (CT) scan of the head showed extradural frontotemporal fluid collection with moderate right to left midline shift. Magnetic resonance imaging (MRI) of the brain showed signs of intracranial hypotension, such as brain sagging and diffuse dural contrast enhancement. Conservative treatment with bed rest, aggressive hydration, steroids, and aminophylline led to progressive neurologic improvement. A systematic literature review was also performed, and previous reported cases were analyzed. Overall, neurosurgeons must be aware of the lumbar drainage–induced hypotension syndrome in skull base surgeries, because immediate diagnosis is essential for therapeutic decision-making. In this setting, conservative management is the first-line treatment as surgery may lead to severe complications.
Keywords: intracranial hypotension syndrome; lumbar drainage; skull base surgery; case report; literature review